Le Bestiaire des vidas et razos : dames et troubadours à figure d’animaux - Cécile Le Cornec Rochelois (Revue des Langues Romanes)
When they presented and commented poems written by troubadours, from the middle of xiiith century, authors of vidas and razos paid attention to the interesting bestiary of these texts. Mentions of animals are among lyric details that inspired them. The bestiary in vidas and razos reveals how their authors used to consider the troubadours and the meaning of their works, more than one century after they have been written. Similitudines, or in other words metaphoric relationships with some animals, are understood actually for what they are. However, other animals don’t obey to the rules of metaphor and take over vidas and razos, in such a way that the troubadour’s life looks like a scene from a bestiary : for instance, Bernart de Ventadorn’s lark or Rigaut de Barbezieux’s elephant, which are embodied in ladies or troubadours. We finally study one famous and special case of lycanthropy : Peire Vidal who became a wolf for love.